Uma noção histórica de intolerância religiosa: as conceituações e o caso dos jesuítas no Brasil Colônia - Rocha, Luciano Vieira (2011)
A study of History as a fundamental subject in Religion Sciences, a field delineated in the first chapter, on the Company of Jesus in Colonial Brazil as a part of the Portuguese state formation. The religion in the modern context is an element which passes by the sacred notion and goes to the State identity as a unified element and social organizer. Portugal has transmitted by the Catholic Church this notion of religion as a luso national identity, and one of its instruments for implementing in the society this belonging feeling to the Portuguese state is the Jesuit catechesis. It is also mentioned the importance of the Catholicism in the formation of the Portuguese National State. The comprehension of religious intolerance as a Jesuit practice in the Modern Age as pattern of the dualistic and Eurocentric world view is highlighted. Concerning the concept of religious intolerance, it was performed a survey of documents and thinkers that during the Modern History until the Contemporaneity have been relevant for the formation of the contemporary mentality. Another important aspect which was analyzed is the practice of the Christianity in the New World, being necessary its flexibility in order to be assimilated.